Post-anthesis dry matter and nitrogen accumulation, partitioning, and translocation in maize under different nitrate–ammonium ratios in Northwestern China - Wu, Bing; Cui, Zhengjun; Zechariah, Effah; Guo, Lizhuo; Gao, Yuhong; Yan, Bin; Liu, Hongsheng; Wang, Yifan; Wang, Haidi; Li, Li (Frontiers in Plant Science, 2024)
An appropriate supply of ammonium (NH4 + ) in addition to nitrate (NO3 -) can greatly improve plant growth and promote population productivity of maize. However, knowledge gaps regarding the mechanisms by how different nitrogen (N) fertilizer sources affect the enzymatic activity of nitrogen metabolism and non-structural carbohydrates during post-anthesis period. Herein, a field experiment across 3-year was carried out to explore the effects of four nitrate ammonium ratio (NO3 -/NH4 + =1:0 (N1), 1:1 (N2), 1:3 (N3), and 3:1 (N4)) on post-anthesis dry matter (DM) and N accumulation, partitioning, transportation and grain yield in maize. The results showed that NO3 -/NH4 + ratio with 3:1 improved enzymatic activity of N metabolism and non-structural carbohydrates accumulation, which strongly promoted the transfer of DM and N in vegetative organs to reproductive organs, and improved the pre-anthesis DM and nitrogen translocation efficiency. The enzymatic activity of nitrate reductase, nitrite reductase, glutamine synthetase, glutamine oxoglutarate aminotransferase, and non-structural carbohydrates accumulation under N4 treatment were increased by 9.30%-32.82%, 13.19%-37.94%, 4.11%-16.00%, 11.19%-30.82% and 14.89%-31.71% compared with others treatments, respectively. Mixed NO3 --N and NH4 + -N increased the total DM accumulation at anthesis and maturity stage, simultaneous decreased the DM partitioning of stem, increased total DM, DM translocation efficiency (DMtE), and contribution of pre-anthesis assimilates to the grain (CAPG) in 2015 and 2017, promoted the transfer of DM in stem to grain.Furthermore, the grain yield demonstrated an increase of 3.31%-9.94% (2015), 68.6%-26.30% (2016), and 8.292%-36.08% (2017) under N4 treatment compared to the N1, N2, and N3 treatments. Overall, this study showed that NO3 -/NH4 + ratio with 3:1 was the recommended for high-yield and sustainability maize management strategy in Northwestern China. Key worlds: mixed NO3 -/NH4 + , maize, grain yield, enzymatic activity, dry matter and nitrogen partitioning and transportation N2 (NO3 -/NH4 + = 删除[悠]: